The reformation of prophecy: early modern interpretations of the prophet and Old Testament prophecy - Pak, G. Sujin (Oxford studies in historical theology, 2018)
Prophecy and the priesthood of all believers -- Prophecy and the radicals: re-thinking prophecy and the prophet contra the radicals -- Prophecy and the pastoral office: Luther and Zwingli -- Prophecy and the teaching office: Bullinger and Calvin -- The prophet, prophecy, and the pastoral office in the next generation -- Old Testament prophecy and Protestant conceptions of sacred history -- Later Lutheran, Swiss Reformed, and Calvinist readings of sacred history in the Old Testament prophets -- Christological exegesis and the interpretation of metaphors in Old Testament prophecy